2013
DOI: 10.1016/j.ymgme.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

An exon 53 frameshift mutation in CUBN abrogates cubam function and causes Imerslund-Gräsbeck syndrome in dogs

Abstract: Cobalamin malabsorption accompanied by selective proteinuria is an autosomal recessive disorder known as Imerslund-Gräsbeck syndrome in humans and was previously described in dogs due to amnionless (AMN) mutations. The resultant vitamin B12 deficiency causes dyshematopoiesis, lethargy, failure to thrive, and life-threatening metabolic disruption in the juvenile period. We studied 3 kindreds of border collies with cobalamin malabsorption and mapped the disease locus in affected dogs to a 2.9 Mb region of homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…17 It is an autosomal recessive trait caused by 2 distinct AMN mutations in Giant Schnauzers 17 and Australian Shepherds. 5 Our group and others recently identified 2 independent CUBN mutations in Border Collies 18,19 and Beagles. 10,20 Although the disease is rare, substantial carrier frequency has been noted in affected breeds 20 and thus disease occurrence is more common regionally.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is an autosomal recessive trait caused by 2 distinct AMN mutations in Giant Schnauzers 17 and Australian Shepherds. 5 Our group and others recently identified 2 independent CUBN mutations in Border Collies 18,19 and Beagles. 10,20 Although the disease is rare, substantial carrier frequency has been noted in affected breeds 20 and thus disease occurrence is more common regionally.…”
Section: Introductionmentioning
confidence: 99%
“…Cubam is a heteromeric, multi ligand, endocytic receptor composed of 2 distinct protein subunits, cubilin (CUBN) and amnionless (AMN) . While several AMN and CUBN mutations occur in humans with I‐GS, only 2 AMN mutations, and most recently, a single CUBN mutation, have been found in 3 different affected dog breeds.…”
mentioning
confidence: 99%
“…The results of our study using IGS‐affected dogs with a known functional defect of cubam but otherwise healthy intestinal tract indicate for the first time that passive intestinal Cbl absorption alone leads to a normal clinical and cellular Cbl status in dogs. This is especially true for the Beagle breed because a recent study showed that CUBN expression was undetectable in tissue samples from an affected dog, whereas in Border Collies with IGS, expression of small amounts of residual CUBN retaining IF‐Cbl binding recently was reported . However, this laboratory finding does not appear to be associated with effective Cbl absorption because all available publications concerning Border Collies with IGS have reported the presence of severe Cbl deficiency …”
Section: Discussionmentioning
confidence: 99%
“…In dogs, selective intestinal Cbl malabsorption, comparable to IGS in humans, has been described in Australian Shepherds, Beagles, Border Collies, and Giant Schnauzers . It is an autosomal recessive trait caused by 2 distinct AMN mutations in Giant Schnauzers and Australian Shepherds, and our group and others recently identified 2 independent CUBN mutations in Border Collies and Beagles . The condition is lethal in affected dogs unless detected and treated appropriately .…”
Section: Introductionmentioning
confidence: 89%